Periviable delivery of a pregnancy in a rudimentary uterine horn: A case report - Katherine E. Coakley; Tyler B. Yang; Judith H. Chung (Elsevier, 2021)
Pregnancy in a rudimentary uterine horn is an extremely rare form of ectopic pregnancy, with an incidence of 1 in 76,000-140,000 pregnancies. Given its high-risk nature, the standard of care is to terminate such pregnancies at the time of diagnosis. This is a case of a nulliparous patient at 23 5/7 weeks of gestation with a new diagnosis of a rudimentary horn pregnancy. She elected to proceed with full intervention for her fetus and was delivered at 24 0/7 weeks after administration of antenatal corticosteroid therapy. While the infant did have some adverse effects related to prematurity, she met developmental milestones and was alive and well at the age of two. Although the standard of care is to manage these cases as ectopic pregnancies, when diagnosed at a periviable gestational age, optimization of fetal status prior to delivery may be an alternative approach to immediate delivery.